UJI KUALITAS KITOSAN DARI LIMBAH TULANG SOTONG DENGAN VARIASI SUHU DEASETILASI - Iin Lidia Putama Mursal; Farhamzah Farhamzah; Ajeng Selistiawati; Dewi Sheyka Meli; Nanda Chaerani; Naufal Muyasyar; Tita Latipah; Vivi Vidia (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Research has been carried out on testing the quality of characteristics chitosan from cuttlefish bone waste with variations in deacetylation temperature. The purpose of this study is to identify the potential of cuttlefish bone as a raw material for producing chitosan and the effect of variations in deacetylation temperature on the quality of the chitosan. The tests of water content, ash content and chitosan solubility values. Solubility test showed that the three samples were soluble in 2% acetic acid. The results of the water content test with variations in deacetylation temperatures of 110 0C, 120 0C, 130 0C were 0.3467%, 0.1063% and 0.0135%, respectively. The ash content of chitosan is 0.2627%, 0.0125% and 0.0060%. The results of testing water and ash content showed a decrease in the value linear within increasing temperature.